2004
DOI: 10.1530/eje.0.1500789
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluorodeoxyglucose positron emission tomography as a diagnostic tool for malignancy of adrenocortical tumours? Preliminary results in 13 consecutive patients

Abstract: Design: This study is a preliminary report on 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake for the characterization of hypersecretory or non-hypersecretory adrenocortical masses in patients without known neoplastic disease, thereby minimizing the presence of adrenal metastases, and without phaeochromocytoma, in comparison with computed tomography (CT) scanning and with iodocholesterol scintigraphy. Methods: Thirteen consecutive patients with an adrenal mass scheduled to have surgery, underwent hormonal explorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 10 publications
2
19
0
3
Order By: Relevance
“…www.endocrinology-journals.org uptake in adrenal adenomas (Tenenbaum et al 2004) but they have shown uptake in adrenal metastases Fig. 6).…”
Section: Ilias Et Al: Imaging Of Adrenal Tumoursmentioning
confidence: 99%
“…www.endocrinology-journals.org uptake in adrenal adenomas (Tenenbaum et al 2004) but they have shown uptake in adrenal metastases Fig. 6).…”
Section: Ilias Et Al: Imaging Of Adrenal Tumoursmentioning
confidence: 99%
“…The quantitative analysis of FDG uptake is performed using standardized uptake values (SUV) or by qualitative visual evaluation with respect to liver uptake. The sensitivity of FDG-PET in identifying malignant lesions varied between 93 and 100% with a specificity between 80 and 100% (54)(55)(56)(57)(58). Necrotic or hemorrhagic malignant adrenal lesions may cause false-negative results showing poor FDG uptake.…”
Section: Epidemiologymentioning
confidence: 99%
“…Thus, (18)-FDG PET scan appears to distinguish between benign and malignant adrenal tumors (Becherer et al 2001, Maurea et al 2001, Tenenbaum et al 2004. This simple, non-traumatic imaging procedure also participates in the extension work-up (Leboulleux et al 2006).…”
Section: Imaging Investigationsmentioning
confidence: 99%